Portaria PRPI nº 71, de 28 de março de 2016 - Marco Aurelio Alves Adao (DMPF-e, Brasília, DF, 29 mar. 2016. Caderno Administrativo, p. 54., 2016)
Altera o art. 1º, da Portaria PR/PI nº 65, de 18 de março de 2016.